ESTRO-ACROP guideline on surface guided radiation therapy. (August 2022) - Freislederer, P.; Batista, V.; Öllers, M.; Buschmann, M.; Steiner, E.; Kügele, M.; Fracchiolla, F.; Corradini, S.; de Smet, M.; Moura, F.; Perryck, S.; Dionisi, F.; et al.
Highlights: First European guideline on Surface Guided Radiation Therapy (SGRT) Collection of criteria for decision-making for procurement of an SGRT system. Overview of staff roles and responsibilities and common and potential errors in SGRT workflows. Recommendations for acceptance and commissioning. Comprehensive guidelines for QA procedures and QA frequency. Abstract: Surface guidance systems enable patient positioning and motion monitoring without using ionising radiation. Surface Guided Radiation Therapy (SGRT) has therefore been widely adopted in radiation therapy in recent years, but guidelines on workflows and specific quality assurance (QA) are lacking. This ESTRO-ACROP guideline aims to give recommendations concerning SGRT roles and responsibilities and highlights common challenges and potential errors. Comprehensive guidelines for procurement, acceptance, commissioning, and QA of SGRT systems installed on computed tomography (CT) simulators, C-arm linacs, closed-bore linacs, and particle therapy treatment systems are presented that will help move to a consensus among SGRT users and facilitate a safe and efficient implementation and clinical application of SGRT.